Typological classification of the Kirov Region's municipalities based on their resource capacities and capabilities for social and economic growth - S. B. Zykova (Аграрная наука Евро-Северо-Востока, 2016)
The article addresses the concept of the sustainable development of a regional municipality and the role of a municipality's factor endowment in fostering social and economic growth. The goal of the research is to get the integrated assessment of the factor endowment of the socio-economic development for the Kirov Region's territories. The integrated assessment was based on grouping the region’s districts by five sets of indicators, which made it possible to assess natural, material and technical, production, human, and financial capabilities for development. Typological classification of the region’s districts by the size of their factor endowments is based on the Kirov Region’s statistical data for 2010 as the starting point of resource availability for development of the region’s municipalities. The monitoring discovered essential differences in the size of the factor endowments between the districts of the region, which should result in the different scenarios for the districts' future development. The districts with a small factor (0.34-0.45) endowment require an immediate attraction of heavy investments from different sources for economic revival in these territories and to prevent depopulation processes. In the districts with a normal factor (0.58-0.69) endowment it is important to overcome the negative trends in economic activities of enterprises, to implement the diversification of their activities and to ensure the population stability. In the districts with the highest factor (0.70-0.82) endowment it is necessary to create conditions for its efficient use and reproduction of population. The importance of the developed classification of the region’s districts by their factor endowments is to get the scientific basis for reasoning the differentiated approach to the influence on the region’s territories by the government and for determining the strategies for their further social and economic development.